Nurses' perceptions of advance directives - Silva, Ernestina (2018)
Objective: To identify nurses perceptions of Advance Directives (AD) and to analyse the in uence of experience with AD on their perception. Material and methods: Quantitative, descriptive, correlational study conducted in a hospital in central Portugal with a sample of 139 nurses, aged 20-60 and in which 78.4% are women and 74% are under 40 years of age. A questionnaire was applied on nurses’ perceptions of AD, their socio-demographic characteristics, and professional experiences with AD. Results: Nurses with 26-30 years of experience have a more critical position with regards to AD (P = .03). Approximately 95% of nurses have no experience of situations where they were given the opportunity for the patient to decide using the AD, nor did they experience situations where the patient has been informed of this right. Most nurses (72.7%) expressed their readiness to re ect with the patient to preparing the AD document and 45.3% would only do so, if the patient or the family requested it. Conclusion: Nurses have little experience with AD. They are available to respect the patient’s will but did not feel able to address the issue on their own initiative. Most agree that the AD can “fail” if the patient does not reevaluate it periodically. Reflection and debate on the ethical issues surrounding AD should be promoted: promoting patient autonomy, care in vulnerable situations, team decisions and conscientious objection.